The Planning Process of “HOMERESC” Home Service System - Nur Fatin Izzati Mamat; Nurdiana Azizan (Malaysian Journal of Science Health & Technology, 2024)
This paper presents the planning process of the HOMERESC mobile application, the home service system. In contemporary times, locating companies or individuals providing home repair services has become increasingly challenging. Home repairing services in Malaysia encompass a range of maintenance and renovation tasks to enhance the condition and functionality of residential properties. Some examples include the Taman Seri Berembang flat building, which was formerly in critical condition. A 22-year-old complex of flats with 30 homes was discovered to be damaged and unsafe to live in. Therefore, a mobile application named "HOMERESC" Home Service System was developed to address all the issues and ensure the welfare of users. The name ‘HOMERESC’ was chosen to represent this application’s ability to "rescue" all damaged homes. An Agile methodology has been used to build this system, ensuring the project’s goals are met and the development process goes smoothly. The implication of the research suggests that the mobile application offers a secure and viable solution for home repair services. In conclusion, the research demonstrates that the HOMERESC mobile application could enhance the safety and welfare of residential property owners.